Role of bone biopsy and deep tissue culture for antibiotic stewardship in diabetic foot osteomyelitis. (10th October 2022) - Hockney, Sara M; Steker, Danielle; Bhasin, Ajay; Krueger, Karen M; Williams, Janna; Galvin, Shannon
Abstract: Objectives: To describe organisms most frequently identified on bone biopsy or deep tissue culture and determine how culture data impacted antibiotic management in patients with diabetic foot osteomyelitis (DFO). Methods: We retrospectively reviewed patients admitted with a diabetic foot ulcer (DFU) between 3 March 2018 and 31 December 2019 and selected for patients diagnosed with infectious osteomyelitis (OM) of the lower extremity. We stratified patients by whether a bone biopsy or deep tissue culture was obtained and compared rates of antibiotic utilization with chi-squared and Fisher's exact tests. Results: Of 305 patients with a DFU, 152 (50%) were clinically diagnosed with DFO. Forty-seven patients received 41 deep tissue cultures and 29 bone biopsy cultures for a total of 70 cultures. Of 45 (64%) positive cultures, 36 (80%) had Gram-positive organisms and 19 (42%) had Gram-negative organisms. MDR organisms were isolated in 7 (15%) patients. Culture data resulted in antibiotic changes in 41 (87%) patients. Therapy was narrowed in 29 (62%) patients and broadened due to inadequate empirical coverage in 4 (9%) patients. Culture data from 18 (40%) patients showed susceptibility to an oral treatment regimen with high bioavailability. There was no significant difference in rates of antibiotic utilization at discharge between patients who underwent bone biopsy or deep tissue culture relative to those who did not (77% versus 75%, P  = 0.86), although less MRSA coverage was used (34% versus 50%, P  = 0.047). Conclusions: In patients with DFO, deep tissue and bone biopsy cultures were infrequently obtained but resulted in targeted therapy changes in most patients. Culture data usually allowed for narrowing of antibiotics but revealed inadequate empirical coverage in a subset of patients.